2019
DOI: 10.1037/cou0000316
|View full text |Cite
|
Sign up to set email alerts
|

Examining therapist effects in relation to clients’ race-ethnicity and gender: An intersectionality approach.

Abstract: Women and Men of Color experience racism in unique and complex ways, just as White Women and Women of Color experience unique forms of sexism (i.e., gendered racism). Traditional analyses of therapists' cultural competence, broadly defined, have yet to examine the effect of intersectionality on the processes and outcomes of psychotherapy. Although previous research suggests that therapists differ in their effectiveness with Racial-Ethnic Minority (REM) clients, no study has examined therapist effects in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Therefore, therapists may attune to only one salient cultural identity, despite their clients’ holding multiple important cultural identities. This aligns with the results of Kivlighan et al (2019), which suggested that there is significant between-therapist variability in terms of their ability to effectively treat clients based on the interaction of both clients’ racial and gender identities. In the present study, this phenomenon is reflected in the finding that therapists are rated highest in terms of cultural humility when clients rated their first most important identity high in terms of saliency, and their second most important identity low, and vice versa (e.g., a high degree of salience discrepancy).…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, therapists may attune to only one salient cultural identity, despite their clients’ holding multiple important cultural identities. This aligns with the results of Kivlighan et al (2019), which suggested that there is significant between-therapist variability in terms of their ability to effectively treat clients based on the interaction of both clients’ racial and gender identities. In the present study, this phenomenon is reflected in the finding that therapists are rated highest in terms of cultural humility when clients rated their first most important identity high in terms of saliency, and their second most important identity low, and vice versa (e.g., a high degree of salience discrepancy).…”
Section: Discussionsupporting
confidence: 84%
“…This may reflect the methodological challenge of obtaining longitudinal data from sufficient numbers of women and men in diverse ethnoracial groups to permit tests of main effects and interactions. In one study, Kivlighan et al (2019) found no main effects of clients’ ethnoracial status or gender and no significant interaction for predicting changes in distress which decreased significantly across the course of psychotherapy. However, both ethnoracial status and the interaction of gender and ethnoracial status contributed to variability in client outcomes (Kivlighan et al, 2019).…”
Section: Barriers To Accessing Mental Health Carementioning
confidence: 98%
“…In one study, Kivlighan et al (2019) found no main effects of clients’ ethnoracial status or gender and no significant interaction for predicting changes in distress which decreased significantly across the course of psychotherapy. However, both ethnoracial status and the interaction of gender and ethnoracial status contributed to variability in client outcomes (Kivlighan et al, 2019). Crucially, the repeated calls to employ evidence-based treatment for mental health problems are necessarily undermined by the limited literature on how the intersection of ethnoracial identity with other identities (e.g., gender, sexual orientation) may impact needs, access, and efficacy.…”
Section: Barriers To Accessing Mental Health Carementioning
confidence: 98%
“…As such, graduates from current clinical programs will and are increasingly serving more and more diverse clients, perhaps most significant of which may include immigrant populations (Iwamasa et al, 2002;Lim & Nakamoto, 2008;Lopez & Bursztyn, 2013; The APA Presidential Task Force on Immigration, 2013;Yznaga, 2008). Further, trainees and clinicians, including supervisors and academic instructors, must examine intersectional diversity in their work (Anders et al, 2021;Kivlighan et al, 2019;Lee & Kealy, 2018).…”
mentioning
confidence: 99%